Knowledge Claims and Struggles in Decentralized Large Carnivore Governance: Insights From Norway and Sweden - Sjölander-Lindqvist, Annelie; Risvoll, Camilla; Kaarhus, Randi; Lundberg, Aase Kristine; Sandström, Camilla (Frontiers in Ecology and Evolution, 2020)
Keywords: large carnivore management1, pastoral communities2, decentralization3, knowledge spheres4, conflicts5. Ensuring sustainable carnivore populations while simultaneously sustaining active and viable pastoral communities creates conflicts that are difficult to resolve. This article examines how different knowledge systems meet and interact in large carnivore governance in Norway and Sweden. Drawing on a broad range of sources, including observations in meetings, public documents, reports and interviews, in addition to local and national newspaper clippings and Internet sites, we study two processes of regional carnivore management (Nordland, Norway and Jämtland, Sweden). We explore how different forms of knowledge have been mobilized, reproduced, transferred and legitimized in policies and regulations in these two processes. Further, we examine the interplay between scientific and experience-based knowledge at different levels and scales in both of the countries. In Norway, ‘clear zoning’ has been established as a basic management instrument to achieve national ‘population goals’ for carnivores. We show how the locally situated knowledge – in our account represented through the Regional Large Carnivore Committee, which includes political parties’ and Sami Parliament representatives – experiences real barriers by being overrun by the national Ministry of Climate and Environment, in their process of revising the carnivore management plan. In Sweden where the management of large carnivores is devolved to regional authorities and stakeholder-based Wildlife Management Delegations, attempts to regionally solve conflicts are often overthrown by the national environmental protection agency or through court cases initiated by the environmental movement. Hence, compromises that potentially could solve conflicts are undermined. The analysis shows that while carnivore governance in both countries are founded on decentralized management authority at the regional level, local actors struggle for their views, experiences and knowledge to be acknowledged and counted as valid in the management process. While the decentralized management model opens for inclusion of different knowledge systems, this system has yet to acknowledge the challenges of knowledge being dismissed or marginalized across governance levels and scales.